1995
DOI: 10.1002/art.1780380507
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine in the treatment of spondylarthropathy

Abstract: Objective. To assess the efficacy and tolerability of sulfasalazine (SSZ) in the treatment of spondylarthropathy .Methods. We conducted a 6-month randomized, placebo-controlled, double-blind, multicenter study of patients with spondylarthropathy whose disease had remained active despite treatment with nonsteroidal antiinflammatory drugs. Patients were treated with SSZ (3 gdday) or placebo. The primary efficacy variables were the physician's and patient's overall assessments, pain, and morning stiffness. End po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(25 citation statements)
references
References 21 publications
0
23
0
2
Order By: Relevance
“…At least ten double-blind studies have evaluated the efficacy of sulfasalazine, but none included patients with IBD arthropathies. A meta-analysis of five randomized controlled studies in 1990 concluded that there are some beneficial effects of sulfasalazine therapy [22] in AS, but this was followed by two large multicenter trials showing that efficacy of this treatment was limited to the peripheral joint involvement of the disease [23,24,25]. While less well evaluated, the use of mesalamine is supported by the results of two small studies [21, 26, 27].…”
Section: Treatmentmentioning
confidence: 79%
“…At least ten double-blind studies have evaluated the efficacy of sulfasalazine, but none included patients with IBD arthropathies. A meta-analysis of five randomized controlled studies in 1990 concluded that there are some beneficial effects of sulfasalazine therapy [22] in AS, but this was followed by two large multicenter trials showing that efficacy of this treatment was limited to the peripheral joint involvement of the disease [23,24,25]. While less well evaluated, the use of mesalamine is supported by the results of two small studies [21, 26, 27].…”
Section: Treatmentmentioning
confidence: 79%
“…At least 10 double-blind studies have evaluated the efficacy of sulfasalazine, but none included patients with IBD arthropathies. A meta-analysis of 5 randomized controlled studies in 1990 concluded that there are some beneficial effects of sulfasalazine therapy [22] in AS, but this was followed by 2 large multicenter trials showing that efficacy of this treatment was limited to the peripheral joint involvement of the disease [23,24,25]. The same limitation (to peripheral joint symptoms) was reported in a recent Cochrane meta-analysis of 11 controlled trials.…”
Section: Treatmentmentioning
confidence: 87%
“…It should be considered that there is a wide diversity of presenting symptoms in AS, and clinical expression varies a lot [21]. It is probable that immunological and other biological parameters show a similar variety in that rheumatic disorder, further influenced by anti-inflammatory drug therapy.…”
Section: Discussionmentioning
confidence: 98%